SELLING THE SIZZLE—MARKETING NATURAL RESOURCE PROGRAMS - Rob Keck (Wildlife Society Bulletin)
Abstract: Natural resource agencies often have difficulty gaining public approval of, and confidence in, their programs. This is often due to poor communications between agencies and their constituents. The return of the wild turkey (Meleagris gallopavo) is a wildlife success story that showcases the importance of developing partnerships between agencies and nongovernmental organizations, as well as using a marketing approach for communicating agency programs to build consensus among constituents. Action steps to successfully gain support for programs include (1) talk: formally and informally; (2) shine the light: learn and communicate what is going on that is good; (3) offer solutions: find ways to help; translate scientific jargon into common words and applications nonscientists can understand; (4) be creative: be positive; and (5) have a plan: designate an agency liaison.